Saccade, Pupil, and Blink Responses in Rapid Eye Movement Sleep Behavior Disorder. Issue 7 (22nd March 2021) - Perkins, Julia E.; Janzen, Annette; Bernhard, Felix P.; Wilhelm, Karén; Brien, Donald C.; Huang, Jeff; Coe, Brian C.; Vadasz, David; Mayer, Geert; Munoz, Douglas P.; Oertel, Wolfgang H.
Abstract: Background: Parkinson's disease (PD) patients exhibit deficits in saccade performance, pupil function, and blink rate. Isolated REM (rapid eye movement) Sleep Behavior Disorder (RBD) is a harbinger to PD making them candidates to investigate for early oculomotor abnormalities as PD biomarkers. Objectives: We tested whether saccade, pupillary, and blink responses in RBD were similar to PD. Methods: RBD (n = 22), PD (n = 22) patients, and healthy controls (CTRL) (n = 74) were studied with video‐based eye‐tracking. Results: RBD patients did not have significantly different saccadic behavior compared to CTRL, but PD patients differed from CTRL and RBD. Both patient groups had significantly lower blink rates, dampened pupil constriction, and dilation responses compared to CTRL. Conclusion: RBD and PD patients had altered pupil and blink behavior compared to CTRL. Because RBD saccade parameters were comparable to CTRL, pupil and blink brain areas may be impacted before saccadic control areas, making them potential prodromal PD biomarkers. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society